Changing landscapes as text: Geography and national education in Singapore. Issue 1 (8th December 2017) - Ramdas, Kamalini; Ho, Elaine Lynn‐Ee; Woon, Chih Yuan
Abstract : Textbooks are a repository for canonical material that serve as important guides for students as they embark on their journey of learning and discovery. In a discipline as varied as Geography, it is often challenging for authors to decide what to include. We negotiate these concerns as editors of a textbook for a course on Changing Landscapes of Singapore, which is taught primarily to non‐Geography majors who are required by the university to acquire knowledge about Singapore before they graduate. This paper discusses how textbook authors often balance a multiplicity of concerns that extend beyond disciplinary content. These concerns are situated within the broader context of how geographical education plays a key role in making student‐citizens critically aware of the trade‐offs in nation‐building projects and encouraged to apply geographical concepts to engage in active and informed public debates.